Influence of chiken manure biochar on microorganisms and plants - G.S. Galieva; P.A. Kuryntseva; P.Yu. Galitskaya; M.Sh. Tagirov; S.Yu. Selivanovskaya (Учёные записки Казанского университета: Серия Естественные науки)
The effect of chicken manure biochar at different temperatures was analyzed. The biochar was introduced at a dose of 1% (w/w) into the soil used to grow wheat and barley plants under laboratory conditions. It was revealed that an increase in the pyrolysis temperatures from 300 °С to 700 °С resulted in a 15 times larger specific surface area of the biochar samples (B300 and B700) and reduced the nitrogen content by 1.4 times. Following the addition of the biochar samples into the soil, the Pmobile level became significantly higher: by 9.5 and 11.5 times, for B300 and B700 respectively. The contents of Ntotal and Kmobile increased less significantly: by 1.6 times on average. At the same time, the abundance of fungal and bacterial communities remained unchanged based on the study of bacterial 16S and fungal 18S rRNA genes. Their respiration and metabolic activity rates, as determined by the Biolog Ecoplate method, did not statistically differ by the end of the experiment. The analysis of plant samples showed that barely was more sensitive to the biochar than wheat. B700 produced the maximum effect on barley and also stimulated its biomass growth. Apparently, the effects produced by the biochars under study diverge due to their different surface areas: the addition of the biochar with the larger specific surface area into the soil enhanced its water-retaining capacity and is, therefore, advantageous for plants.